Effectiveness of health education in improving knowledge and attitude towards toxoplasmosis among pregnant women in Al Najaf, Iraq - Ibadi, Atheer Kadhim (2016)
The aim of this study is to determine the effect of intervention by health education on the knowledge and attitude on toxoplasmosis among pregnant women with toxoplasmosis in Al- Najaf Al- Ashraf – Iraq-2014. The study compared the scores of knowledge and attitudes between the baseline against the first and second posttests and within three stages and groups, and determine the association of these factors with their sociodemographic characteristics, both Experiment and Control groups. Intervention study design, and a simple random sampling technique was used to select the 340 respondents, who were patients from gynecological clinic from three hospitals. Data was collected from 1st June to 31st October 2015 using a structured pre-tested questionnaire in Arabic language and the response rate was 100 %. The results of this study showed that most of the respondents were housewife, young, had low level of education and live in urban area. At base line there was no significant statistical differences of score between both groups in terms of the overall knowledge on toxoplasmosis. However, the knowledge score of both groups became different statistically at first and second posttests. Findings on the attitude showed that both groups had positive attitude towards toxoplasmosis at baseline and first posttest. However, at second posttest the attitude of the Control Group became negative, whereas the attitude of the Experimental Group remained positive. There was statistically significant difference of the mean score of knowledge between both groups in all different stages of data collections. Repeated measurement using ANOVA with a Greenhous-Geisser correction showed that the mean score according to all items of knowledge on toxoplasmosis infection were differed significantly within time and also differed significantly in the interaction between groups. The same test also showed that the mean score of attitudes on toxoplasmosis were significantly different within baseline, first posttest, and second posttest and also differed significantly within the time between groups. In conclusion, this study showed that the level of knowledge and attitude related to toxoplasmosis among the pregnant women infected with toxoplasmosis in Al-Najaf province is unsatisfactory at the baseline, but it became better after they were given health education on toxoplasmosis.